Healthcare business intelligence : a guide to empowering successful data reporting and analytics - Madsen, Laura, 1973- (Hoboken, New Jersey : John Wiley & Sons, Inc., 2012)
"This book will be constructed as a guidebook for healthcare organizations that are attempting BI/DW. It will address the primary functions of a business intelligence capability and how BI can ease the increasing regulatory reporting pressures on all healthcare organizations. Also included will be tables, checklists and a few forms. Tenative chapter contents: Chapter 1: What is Healthcare BI? Chapter 2: The Five Disciplines of Business Intelligence Chapter 3: The Importance of ETL Chapter 4: Starting with Data Governance Chapter 5: Creating a BI team Chapter 6: Data Modeling for Healthcare Chapter 7: Gaining Support for your BI program Chapter 8: Ensuring good User Adoption Chapter 9: Marketing Your BI Program Chapter 10: Maintaining Your BI Program"--
Business intelligence -- The tenets of healthcare BI -- Data quality -- Leadership and sponsorship -- Technology and architecture -- Providing value -- Gauging your readiness for BI -- Future trends in healthcare BI -- Putting it all together.
Includes index.
Print version record and CIP data provided by publisher.
Includes bibliographical references and index.
John Wiley and Sons
Keywords: Medical records -- Management; Business intelligence; Information resources management; Forms and Records Control; Medical Records Systems, Computerized; Information Management; x; Gestion de l'information.; BUSINESS & ECONOMICS -- Information Management; Information resources management; Business intelligence; Medical records -- Management